The effect of care receivers' dysphagia severity on caregiver burden among family caregivers. Issue 10 (26th August 2022) - Suzuki, Mizue; Kimura, Yosuke; Otobe, Yuhei; Koyama, Shingo; Terao, Yusuke; Kojima, Iwao; Masuda, Hiroaki; Tanaka, Shu; Yamada, Minoru
Abstract : Introduction: Dysphagia has received much attention as a factor that affects caregiver burden. However, few studies have examined how its severity can affect caregiver burden. This study aimed to examine the effect of dysphagia severity on caregiver burden. Methods: A cross‐sectional online survey was carried out among family caregivers. We assessed caregiver burden using the Zarit Burden Interview. The dysphagia severity was assessed using the Functional Oral Intake Scale, and the caregivers were divided into three groups based on care receivers' oral intake status (levels 1–3: tube‐feeding group; levels 4–6: texture‐modified food group; level 7: normal group). To investigate the relationship between caregiver burden and dysphagia severity, univariable and multivariable logistic regression analyses were applied to caregiver burden. Results: The Zarit Burden Interview was significantly higher in the texture‐modified food group, and the proportions of high caregiver burden reached 25.2%, 39.5% and 23.4% in the normal group, texture‐modified food group and tube‐feeding group, respectively. The multivariable analyses applied to caregiver burden (reference, normal group) showed that the texture‐modified food group was significantly associated with caregiver burden (OR 1.55, 95% CI 1.04–2.32), whereas the tube‐feeding group had no relationship with caregiver burden (OR 0.68, 95% CI 0.31–1.49). Conclusions: Our study showed that the intake of texture‐modified food significantly affected caregiver burden even after adjusting for confounding factors, whereas the use of tube feeding did not increase caregiver burden. These results suggest that it is necessary to consider dysphagia severity to reduce dysphagia‐related caregiver burden. Geriatr Gerontol Int 2022; 22: 870–875 . Abstract : This study investigated the effect of care receivers' dysphagia severity on caregiver burden among family caregivers. Texture‐modified food intake had a significant effect on caregiver burden even after adjustment for confounding factors; however, the use of tube feeding did not increase caregiver burden, which was similar to that of caregivers of patients without dysphagia. These results suggest that dysphagia severity might be considered to reduce dysphagia‐related caregiver burden effectively.